Odpowiedzi

2010-03-10T18:28:13+01:00
-3x=7
3x=-7
x=-7/3
x=-2⅓

2x=1/5
x=1/10

1,2x=4,8
x=4

-(2x-1)=4
-2x+1=4
-2x=4-1
2x=-3
x=-1½

2(x+1)=x
2x+2=x
x=-2

2t-(3t+1)=6
2t-3t-1=6
-1t=7
t=-7

2010-03-10T18:29:16+01:00
-3x=7
x=7:(-3)
x= -2 1/3

2x=1/5
x=1/5 :2
x=1/10

1,2x=4,8
x=4,8 : 1,2
x=4

-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3
x=3:(-2)
x=-1,5

2(x+1)=x
2x+2=x
2x-x=-2
x=-2

2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7
t=-7

2010-03-10T18:31:34+01:00
Rozwiąż równania:
a -3x=7
b 2x=1/5
c 1,2x=4,8
d -(2x-1)=4
e 2(x+1)=x
f 2t-(3t+1)=6

a
-3x=7/:(-3)
x=-7/3
x= -2 1/3
b
2x=1/5 / :2
x=1/5 * 1/2
x= 1/10
c
1,2x=4,8/:1,2
x=4
d
-(2x-1)=4
2x+1=4
2x=3/:2
x=3/2
x=1 1/2
e
2(x+1)=x
2x+2=x
x=-2
f
2t-(3t+1)=6
2t-3t-1=6
t-1=6
t=-6

ale głowy za tę obliczenia sobie uciąć nie dam :)